If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2y + 1) + (3x + -6) = 2 + x Reorder the terms: (1 + 2y) + (3x + -6) = 2 + x Remove parenthesis around (1 + 2y) 1 + 2y + (3x + -6) = 2 + x Reorder the terms: 1 + 2y + (-6 + 3x) = 2 + x Remove parenthesis around (-6 + 3x) 1 + 2y + -6 + 3x = 2 + x Reorder the terms: 1 + -6 + 3x + 2y = 2 + x Combine like terms: 1 + -6 = -5 -5 + 3x + 2y = 2 + x Solving -5 + 3x + 2y = 2 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -5 + 3x + -1x + 2y = 2 + x + -1x Combine like terms: 3x + -1x = 2x -5 + 2x + 2y = 2 + x + -1x Combine like terms: x + -1x = 0 -5 + 2x + 2y = 2 + 0 -5 + 2x + 2y = 2 Add '5' to each side of the equation. -5 + 2x + 5 + 2y = 2 + 5 Reorder the terms: -5 + 5 + 2x + 2y = 2 + 5 Combine like terms: -5 + 5 = 0 0 + 2x + 2y = 2 + 5 2x + 2y = 2 + 5 Combine like terms: 2 + 5 = 7 2x + 2y = 7 Add '-2y' to each side of the equation. 2x + 2y + -2y = 7 + -2y Combine like terms: 2y + -2y = 0 2x + 0 = 7 + -2y 2x = 7 + -2y Divide each side by '2'. x = 3.5 + -1y Simplifying x = 3.5 + -1y
| 6-6x=5x-9x-2x | | 8x/7-3/4=6/2-4x/4 | | 3x+-3=180 | | (2x+4)(x+4)=196+3x | | 10m+6=6m+30 | | x-15=x/77 | | -4p-12=12 | | w+2.9=6.4 | | z^2=-2z-14 | | -3/8t=1/6 | | y=20-3(1) | | g=y-cx | | 8(3n+3)=8(6n+3)+2 | | 3(1.5x+9)= | | 2(3x-2)=3(4x+5)+7X | | 144x=3268.80 | | 5x-12+x=-13 | | 4/3x3.14x3.04^3 | | -4p+8(p+3)=4(p-8)+2 | | 6(x+4)-3x=11 | | f(2.5)=2x^2-3+7 | | (4x-15)+(5x+11)+(5x+5)+(6x+19)=360 | | -6.5-4x-1.6-3x=-6+9.8 | | 7(x^2)-2=5x | | 8xt=32 | | 2(5x+4)-2(9x+2)= | | 7n-(1+7n)=3(n-7)-7n | | 72x(3/2)n | | 30x^2-114x+108=0 | | n+9=25 | | 19h+1.50=15+2.75 | | (X-5)/4=-20 |